Inhibition of larval growth of Dαcus oleαe by topical application of streptomycin to olives - Tzanakakis, Μ.Ε.; Prophetou, D.Α.; Vassiliou, G.N.; Papadopoulos, J.J. (ENTOMOLOGIA HELLENICA, 1983)
Olives of four varieties were oviposited by females of Dacus oleae (Gmelin) (Diptera: Tephritidae). One to four hours or one day later, a 5 μl drop of streptomycin sulphate solution in tap water was applied to the oviposition hole. If applied 1-4 hours after oviposition, concentrations of 0.1, 0.3, or 1% were equally effective, inhibiting larval growth in over 85% of the olive fruits. If applied one day later, the 0.1% concentration was less effective, while the 0.3 and 1% ones retained their high effectiveness. With 2 μl drops, inhibition was not significantly lower than with 5 μl drops. The addition of 0.05% or 0.5% Agral 90 a spreader-wetter, had an activating effect, causing a substantial and significant increase of the percent inhibition.